Analysis of soil quality in various land uses in the Central Rembangan micro-watershed, Indonesia - Hermiyanto, Bambang; Budiman, Subhan Arif; Basuki, Basuki; Hafizh, Muhammad; Maharani, Marcellia; Hadi, Syamsul (Journal of Degraded and Mining Lands Management, 2026)
Land degradation due to land use change threatens soil quality and watershed function in Java, Indonesia. This study aimed to evaluate soil quality across various land-use types in the Central Rembangan micro-watershed, East Java, Indonesia, using the Soil Quality Index (SQI) approach based on Principal Component Analysis (PCA). Soil samples were collected from 18 Land Mapping Units (LMUs). The LMU represents a combination of three types of land use, namely rice fields, plantations, and dryland agriculture. The LMU includes six slope classes, namely 0-3%, 3-8%, 8-15%, 15-25%, 25-40%, and >40%. The PCA analysis identified nine key indicators as the Minimum Data Set (MDS). These indicators include soil porosity, permeability, total nitrogen, exchangeable Mg, C/N ratio, soil pH, particle specific gravity, electrical conductivity (EC), and cation exchange capacity (CEC). The SQI value ranges from 0.50 to 0.77. The SQI value shows a significant difference between land use types at p<0.10. The rice field system has the highest SQI value of 0.68±0.09. The plantation system has an SQI value of 0.61±0.06. The dryland agricultural system has an SQI value of 0.57±0.09. Spatial analysis showed that 60% of micro-watershed areas have good soil quality. The good soil quality areas are located in the upstream part which is dominated by forest and plantations. As many as 40% of micro-watershed areas have moderate soil quality. Soil porosity and soil permeability are major contributors to soil quality in all types of land use.